2009
DOI: 10.1002/adma.200802589
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer‐ and Nanometer‐Sized, Single‐Crystalline Ribbons of a Cyclic Triphenylamine Dimer and Their Application in Organic Transistors

Abstract: A cyclic triphenylamine dimer with high crystallinity is demonstrated. Micrometer‐ and nanometer‐sized single‐crystalline ribbons are easily produced by a physical vapor transport technique. Field‐effect transistors of the ribbons exhibit mobilities up to 0.05 cm2 V−1 s−1. The mobility of the devices depends greatly on the size of the ribbons: the smaller the ribbons, the higher the mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…From the preceding sections on the theory of nucleation and thin film growth, it is evident that this physical phenomenon is quite complex and there are several factors that influence film formation. Again, pentacene has been established as the archetypal semiconductor to study the effects of various deposition parameters,2, 28, 30, 36, 37, 59–62, 72–76 although some groups have also investigated the growth of thiophene and napthalene derivatives 45, 77–84. The most common parameters are deposition rate, substrate temperature, substrate surface chemistry, and surface roughness.…”
Section: Effects Of Deposition Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…From the preceding sections on the theory of nucleation and thin film growth, it is evident that this physical phenomenon is quite complex and there are several factors that influence film formation. Again, pentacene has been established as the archetypal semiconductor to study the effects of various deposition parameters,2, 28, 30, 36, 37, 59–62, 72–76 although some groups have also investigated the growth of thiophene and napthalene derivatives 45, 77–84. The most common parameters are deposition rate, substrate temperature, substrate surface chemistry, and surface roughness.…”
Section: Effects Of Deposition Parametersmentioning
confidence: 99%
“…There are several other methods employed by a variety of groups to fabricate OTFTs based on self assembly on electrodes or controlled growth from electrodes. Hu et al grew organic semiconductor nanowires and recently demonstrated crosswire circuits 12, 20, 80, 132. Lee et al and others have also studied the effect of electrode roughness on the morphology of the deposited organic semiconductor in bottom contact transistors 133.…”
Section: Controlled Growth By Surface Roughness Surface Patterninmentioning
confidence: 99%
“…[28] We also found that the smaller the crystal, the higher the mobility observed in SCFETs based on crystalline ribbons of a cyclic triphenylamine dimer. [29] This is also a result of the increase in quality when the crystal size is reduced. In a one-dimensional crystal the electrical transport should be more easily interrupted by the defects, whereas in a two-dimensional crystal the influence of the defects along the p-p stacking direction will be compensated by the electrical transport along other directions.…”
mentioning
confidence: 97%
“…Using PVT methods, the crystal growth control was obtained by Hu et al based on single crystal micro/nanoribbons of compound 2 [35] (as shown in Figure 2 and Table 1). FETs based on individual ribbons showed mobilities up to 0.05 cm 2 /(V s).…”
Section: Physical Vapor Transport (Pvt)mentioning
confidence: 99%